Microwave dielectric properties of CaTiO3-Ca(Al1/2Ta1/2)O-3 ceramics - Kucheiko, S; Choi, JW; Kim, HJ; Jung, HJ (AMER CERAMIC SOC, 1996)
The microwave dielectric properties of CaTi1-x(Al1/2Ta1/2)(x)O-3 solid solutions (0.3 less than or equal to x less than or equal to 0.5) have been investigated. The ceramic samples had perovskite structures similar to CaTiO3,. The partial substitution of Ti4+ by a coupled Al3+/Ta5+ permitted improvement of the quality factor e. The dielectric constant (epsilon(r)) and temperature coefficient of resonant frequency (tau(f)) decrease rapidly with an increase of x. A new high-quality microwave dielectric material was found at x = 0.46 with epsilon(r) = 46.5, Q . f = 27300 GHz, and tau(f) = 0 ppm/degrees C. The relationship between microstructures and dielectric properties is presented.
Keywords: COMPLEX PEROVSKITE; FREQUENCIES; CONSTANT; CA